Statistics and data analysis for the behavioral sciences - Dunn, Dana S. (Boston : McGraw Hill Higher Education, 2001)
The author combines the quantitative aspects of statistics with written explanations of what the results of statistical tests mean in a way that students will understand it.
Includes bibliographical references and indexes.
uaj 23/09/2014
Loan
Keywords: Psychometrics; Psychology; Statistics - data analysis